Soil and Land Use Pattern of a Part of U.P. Tarai and Bhabar Forest-an Aerial-photo Interpretation - Mathur, Alok; Sharma, A. K.; Rathore, T. R.; Prakash, Om (Indian Forester, 1984)
Soils and land use pattern were studied ia a part of Nainital Tarai and Bhabar Forest, Uttar Pradesh. The objectives of the study were to examine feasibility of using aerial photographs as base map for delineating soli boundaries and land use patterns, to characterise and classify the soils and to study their genisis. Reliable stereoscopic interpretation of aerial photographs for accurately delineating soil boundaries could be possible only for the areas which were either under cultivation or under new plantation. In remaining area under thick forest and grass vegetation only random field checks for studying morphological properties of soils were made. The boundaries of existing land use pattern could be easily delineated on aerial photographs and were correlated by field checks. Three distinct soil series namely, Baurkbatta, Dauli and Lalkuan were identified in the whole area but their mapping could be done only for area under cultivation. Characteristics, clasiffication and genesis of tbese series were studied. Baurkhatta series was a coarse loamy, mixed, hyperthermic Aquic Hapludoll. Daull was coarse loamy, mixed, hyperthermic. Mollie Aeric Hapiaquept and Laikuan was a loamy skeletal, mixed, hyperthermic Typic Eutrochrept. The local topography and to some extent kind of vegetation were the factors determining soli genesis. Of the total mapped area (1313.12 ha). Baurkhatta, Daull and Lalkuan series occupied 33.4,43.9 and 22.7 per cent, respectively. Of the major land uses, about 43 per cent area was under forests in which Eucalyptus, Sal and Sisam were the main tree species; 3.5 per cent area was under grassland where johnson, tiger and kamal were the main grasses; about 11 per cent area was under river bed and roads and rest 9.5 per cent was under cultivation where new plantation was being planned. Soils under the influence of grass vegetation had thicker, darker and higher base status horizons than those of soils under forest vegetation.